Deoxythymidine–Pterin Fluorescent Adduct Formation through a Photosensitized Process - Estébanez, Sandra (2017)
A new fluorescent compound was isolated from UVA-irradiated aqueous solutions containing pterin (Ptr) and 2′deoxythymidine (dT) in anaerobic conditions. Pterins are widespread in living systems in small amounts, but they are accumulated in some pathological situations. Under UVA radiation, pterins are photochemically active, fluorescent, and photosensitize the generation of singlet oxygen [1O2(1Δg)]. The isolated compound was structurally characterized by using liquid chromatography coupled to tandem mass spectrometry, and its photophysical properties were studied with the time-correlated single-photon-counting technique. The molecular weight and the analysis of the fragmentation correspond to a molecule where the pterinic moiety is attached to the thymine nucleobase. The product exhibits photophysical properties similar to those of Ptr, including relatively high fluorescence and 1O2 production quantum yields.